Avaliação do desempenho acústico de um sistema de construção modular: estudo de caso - Ribeiro, Rodrigo Scoczynski (2015)
The objective of this study is evaluate the modular and industrialized building system’s acoustic performance through the simplified field method indicated by ABNT NBR 15575-4:2013 and ISO 10052: 2004, analyzing the internal and external vertical seals for air noise insulation and comparing with previous analyzes in other approaches. The world construction industry is in a dedicated time to the pursuit and implementation of sector modernization strategies in order to reduce costs and minimize waste, invested in sustainable buildings. It’s is necessary studies based on the parameters of NBR 15575-4: 2013 for the proper characterization of building technologies that emerge and are still new to the sector. The standard implies a series of requirements and recommendations, such as the acoustic comfort, which will be addressed in this work. The methodology used was based on the simplified method guided by ISO 10052: 2004. Two buildings were analyzed, with 40,0m2 each. One of them is a two-story house, and the other is a ground floor building. Measurements of sound pressure levels were made in the rooms and on the frontages, and measurements of the reverberation time of rooms. After the measurements were made analyzes with test "t" student. Compared to the standards of other countries, it was realized that the ABNT NBR 15575-4: 2013 has soft values, and that even so, the current Brazilian construction techniques, for the most part, can not reach them. Through these results, it was noticed an efficiency about the isolation airnoise in modular and industrialized buildings compared to buildings of other construction techniques. It follows, then, that the floor and the ground floor building comply with the performance levels established by ABNT NBR 15575-4: 2013.